Aggressiveness and genetic variability of Fusarium graminearum populations from the main wheat production area of Argentina - Malbrán, Ismael (2018)
Objectives: Differences in aggressiveness and mycotoxin production were previously found among isolates of Fusarium graminearum, the main incitant of Fusarium head blight (FHB) of wheat, from Argentina. This study aims at evaluating the genetic diversity present in these isolates and its relationship with their aggressiveness. Methods: Inter-simple sequence repeats polymerase chain reaction (ISSR-PCR) was used to asses the genetic variability present in 112 F. graminearum isolates from 28 localities of Buenos Aires Province, Argentina. The analysis of molecular variance (AMOVA) was performed to examine the population structure. Results: F. graminearum populations from Argentina showed a large genotypic variability. Seventy seven percent of the isolates included in the analysis were identified as a unique haplotype. The largest part of this variation resulted from genetic differences within (89%) rather than between populations (11%). The constructed dendrogram showed no genotype clustering according to geographic origin or aggressiveness of the isolates. Conclusions: A high genetic heterogeneity was found in the F. graminearum populations from Argentina. This diversity can possibly reflect the occurrence of high frequencies of sexual outcrosses in the field and gene flow.